Pelatihan Konseling Kesehatan Remaja untuk Meningkatkan Efikasi Diri Konselor Sebaya pada Siswa Sekolah Menengah Atas - Muhammad Arif Rizqi; Fuad Nashori; Yulianti Dwi Astuti (JIP (Jurnal Intervensi Psikologi), 2017)
The purpose of this study was to evaluate the effectivity of Adolescent Health Counseling Training in improving peer counselor self-efficacy on high school students. There were three participants enrolled thisstudy.Peer counselor self-efficacy was measured by using self-efficacy scale. Data were analyzed using nonparametric Wilcoxon testto see differences in peer counselor self-efficacy before and after intervention. The result show no significant effect of Adolescent Health Counseling Training in Improving peer Counselor (p=0,150). Qualitative analyzed showed that self-efficacy of peer counselor improves peer counselor self-efficacy after intervention. Keywords: Peer Counselor, Adolescent Health Counseling Training, Self-Efficacy